Impact of Inflation, Interest Rate, And Use of Electronic Money on The Amount of Money Circulating in Indonesia During the Period 2015–2022 - Shinta Ainur Rahmadani; Peny Cahaya Azwari; Syamsiar Zahrani (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The study aims to determine the impact of inflation, interest rates, and the use of electronic money on the amount of money circulating in Indonesia in the period 2015-2022 both partially and simultaneously. This research uses quantitative research methods. The research model used in the study is the Ordinary Least Square (OLS) model or double linear regression. Data used in this study is data time series in Indonesia from the year 2015-2022 obtained from the official website of the Bank of Indonesia and the Central Statistical Authority which comprises 96 samples. The results of this study show that inflation has a significant and related negative influence on the amount of money circulating in Indonesia during the period 2015-2022. This is demonstrated by a double linear regression analysis with a coefficient of -269859.5. The t-count value of -7.918753 is smaller than the t-table value of 1.66159. The significance value comparison obtained is 0.0000, which is smaller than 0.05.  The same is true of the interest rate has significant and relevant negative impact on the quantity of money in circulation in Indonesia between 2015 and 2022. This is demonstrated by double linear regression analysis, with a coefficient value of -172870.6. The t-count value is -3.979156; this value is smaller than the t-table of 1.66159. The significance ratio obtained is 0.0001, which is smaller than 0.05.  While the use of electronic money has a significant and positive impact on the amount of money circulating in Indonesia in the period 2015-2022. This is demonstrated by double linear regression analysis, with a coefficient value of 0.028128. The t-count value of 21.69518, this value is greater than the t-table of 1.66159. The relative value of significance obtained is 0.0000, smaller than 0.05. From the results of this research, it is also known that the value of Adjusted R-Squared is 0.926799, this means that 92.6% of the money supply in Indonesia for the 2015-2022 period is influenced by inflation, interest rates and the use of electronic money. The remaining 7.4% is explained by other variables not explained in this study.